Perspectives of Technical Assistance Providers on Nature-Based Solution Practices in North Carolina, USA - Courtney B. Deviney; Rajan Parajuli; Frederick W. Cubbage; Erin O. Sills; Robert E. Bardon; Stephanie Chizmar; Kathleen McGinley (Environmental Management, 2026)
Nature-based solutions (NBS) are increasingly promoted in agricultural and forestry policy, yet their effectiveness depends on technical assistance providers (TAPs) who translate policy guidelines into land management decisions. Drawing on Diffusion of Innovations and Value–Belief–Norm frameworks, this study examines how TAPs’ professional backgrounds, organizational affiliations, regional contexts, and management experiences shape their knowledge, perceived importance, and promotion of NBS. A web-based survey of 101 TAPs in North Carolina was analyzed using Spearman correlations and logistic regression. While 79% of respondents reported familiarity with NBS, only about half of them actively promoted these practices. Adoption pathways varied across sectors. In agriculture, recent management experience was linked to greater emphasis on ecosystem services and higher likelihood of promoting NBS. In forestry, engagement was stronger for establishment and periodic management practices than for timber-oriented activities. These findings highlight the need for sector-specific outreach strategies that account for TAPs’ professional contexts and institutional settings to improve NBS adoption on working lands.

Planning for the future of forests: What drives landowners' estate planning decisions in the Southern United States? - Ana Cubas-Baez; Rajan Parajuli; Erin O. Sills; Frederick Cubbage; Gregory Frey; Kurt Smith (Journal of Environmental Management, 2026)

Current trends in silvopastoral systems - Pablo L. Peri; Julián Chará; Carolina Viñoles; Adriana Bussoni; Frederick Cubbage (Agroforestry Systems, 2024)

Characterizing Community Forests in the United States - Reem Hajjar; Kathleen McGinley; Susan Charnley; Gregory E Frey; Meredith Hovis; Frederick W Cubbage; John Schelhas; Kailey Kornhauser (Journal of Forestry, 2024)
Research on community forests (CFs), primarily governed and managed by local forest users in the United States, is limited, despite their growth in numbers over the past decade. We conducted a survey to inventory CFs in the United States and better understand their ownership and governance structures, management objectives, benefits, and financing. The ninety-eight CFs in our inventory are on private, public, and tribal lands. They had various ways of soliciting input from, or sharing decision-making authority with, local groups, organizations, and citizens. Recreation and environmental services were the most important management goals, but timber production occurred on more than two-thirds of CFs, contributing to income on many CFs, along with a diversity of other income sources to fund operations. We discuss the difficulties in creating a comprehensive CF inventory and typology given the diversity of models that exist, reflecting local social and environmental conditions and the bottom-up nature of community forestry in the United States. Study Implications: Despite their small footprint in the United States, community forests are a rapidly developing model of forest ownership, governance, and management that helps protect forestlands and open space and demonstrates how market and nonmarket forest goods and services can be produced for broad and enduring community benefits. This study inventories and characterizes community forests in the United States to increase understanding of this model, its prevalence, and its potential. It provides a baseline of information that serves as a foundation for further exploration and research on the impacts and contributions of community forests.

Eucalyptus benthamii Maiden et Cambage growth and wood density in integrated crop-livestock systems - Silvano Kruchelski; Jonathan William Trautenmüller; Leonardo Deiss; Rômulo Trevisan; Frederick Cubbage; Vanderley Porfírio-da-Silva; Anibal de Moraes (Agroforestry Systems, 2021)

State Cost-Share Programs for Forest Landowners in the Southern United States: A Review - Stephanie J Chizmar; Rajan Parajuli; Robert Bardon; Frederick Cubbage (Journal of Forestry, 2021)
The largest concentration of state-level forest cost-share programs in the United States can be found in the southern states. Since the inception of the first programs in the 1970s, the state-level forest cost-share programs in the US South have acted as models for the rest of the country. Cost-share programs compensate landowners through direct reimbursements to address barriers such as limited owner capital and cash flow in the initial years of investment. Through a review of the literature and progress reports from southern state forestry agencies, we qualitatively assessed state-level cost-share programs and their status in the southern states. We identified the common themes in the literature related to cost-share programs: market, nonmarket, and landowners’ perceptions and knowledge. Many of the programs enacted between the 1970s and 1980s aimed to ensure a sustainable timber supply, a market good, from private forestlands. A few of the programs enacted more recently compensate landowners for nonmarket benefits such as forest health or soil and water conservation. Two of the nine available programs are practically inactive in recent years because of a lack of funding. We discuss current prospects regarding funding, partnerships, and broadening the focus of incentives to cover forest-based ecosystem services. Study Implications Regionally, cost-share programs in the US South differ in eligibility criteria, funding source and status, and resource management objectives. The majority of state-level cost-share programs in the US South were enacted 30 to 50 years ago. The first cost-share programs were designed to support a continued timber supply from private forestlands, but a few recent programs have expanded their objectives to protect forest health and soil and water quality. Forest-based ecosystem service markets, specifically reforestation to capture atmospheric carbon dioxide and provide clean air and water, have become more prevalent in recent years. Funding for forest commodity incentive programs is a continual challenge. New funding sources and new programs are crucial to meet demands for incentives for landowners to provide both timber and ecosystem services outputs.

Corrigendum to: Forest Sector Research and Development Capacity - Kathleen A Mcginley; Richard W Guldin; Frederick W Cubbage (Journal of Forestry, 2021)

Projecting global and regional outlooks for planted forests under the shared socio-economic pathways - Jaana Korhonen; Prakash Nepal; Jeffrey P. Prestemon; Frederick W. Cubbage (New Forests, 2021)
There is rising global interest in growing more trees in order to meet growing population, climate change, and wood energy needs. Using recently published data on planted forests by country, we estimated relationships between per capita income and planted forest area that are useful for understanding prospective planted forest area futures through 2100 under various United Nations Intergovernmental Panel on Climate Change-inspired Shared Socio-economic Pathways (SSPs). Under all SSPs, projections indicate increasing global planted forest area trends for the next three to four decades and declining trends thereafter, commensurate with the quadratic functions employed. Our projections indicate somewhat less total future planted forest area than prior linear forecasts. Compared to 293 million ha (Mha) of planted forests globally in 2015, SSP5 (a vision of a wealthier world) projects the largest increase (to 334 Mha, a 14% gain) by 2055, followed by SSP2 (a continuation of historical socio-economic trends, to 327 Mha, or an 11% gain), and SSP3 (a vision of a poorer world, to 319 Mha, a 9% gain). The projected trends for major world regions differ from global trends, consistent with differing socio-economic development trajectories in those regions. Our projections based on empirical FAO data for the past 25 years, as well as those by other researchers, suggest that achieving the much more ambitious global planted forest targets proposed recently will require exceptional forest land and investment supply shifts.

Structural Changes on Pulpwood Market in the US South: Wood Pellets Investments and Price Dynamics - Bruno Kanieski da Silva; Frederick W Cubbage; Robert C Abt (Forest Science, 2019)
We investigated the impact of wood pellet mills on pulpwood price structure in the US South. Rather than focusing exclusively on price elasticities, we progress by examining how wood pellet production has affected the spatial transmission of pulpwood prices. Pairwise price ratios were modeled using smooth transition regression to identify changes in the cointegration (linkage) between markets over time. A logistic model was fitted to estimate market linkages as a function of market distances, industry concentration, and capacity of pellet wood production. Results show that the US South is not composed of market clusters, but each market pair has a particular relation. Distance and wood pellet production capacity are the only factors driving market linkages; the pulp and paper industries did not affect market structure changes. Our research suggests spatial price transmission varies over time, and pellet mills have caused a structural change in the pulpwood prices in the US South.

An analysis of potential investment returns of planted forests in South China - Pu Zhang; Youjun He; Yiming Feng; Rafael De La Torre; Hongyan Jia; Jixin Tang; Frederick Cubbage (New Forests, 2019)

Forest Sector Research and Development Capacity - Kathleen A McGinley; Richard W Guldin; Frederick W Cubbage (Journal of Forestry, 2019)
Current trends in the nation’s forest-sector research capacity were analyzed in terms of funding and number of scientists, and compared with prior data in the National Research Council’s 2002 report, National Capacity in Forestry Research. The total number of professors at institutions with academic programs accredited by the Society of American Foresters, research scientists at the USDA Forest Service, and forest researchers in forest industry decreased approximately 12 percent since 2002. In 2016, there were an estimated 1,224 professors and 540 Forest Service research scientists, for a total of 1,764 scientists. Total estimated research funding in 2015 for universities, private sector, and USDA Forest Service, including appropriations from federal grant programs from the USDA National Institute for Food and Agriculture, National Science Foundation, National Aeronautics and Space Administration, and Department of Energy was US$598 million—a nominal increase over 2002, but a decrease when accounting for inflation. The proportion of reported scientists’ disciplines shifted notably from production subjects to broader ecosystem services and forest health subjects, as well as from more applied to more fundamental or basic research. The data indicated that the nation’s forest research capacity continues to erode, leading to declines in research development and innovation, and putting at increasing risk the future health and productivity of America’s forests.

Diverse strategies for integration of forestry and livestock production - Adriana Bussoni; Jorge Alvarez; Frederick Cubbage; Gustavo Ferreira; Valentin Picasso (Agroforestry Systems, 2019)

Modeling the Financial Potential of Silvopasture Agroforestry in Eastern North Carolina and Northeastern Oregon - Sonia R Bruck; Badege Bishaw; Tamara L Cushing; Frederick W Cubbage (Journal of Forestry, 2019)
Silvopasture is the planned and managed agroecosystem in which forage, livestock, and woody perennials are integrated “either simultaneously or sequentially on the same parcel of land.” Silvopasture can help mitigate anthropogenic climate change through carbon sequestration in perennial vegetation. We examined silvopasture, forest, and pasture systems in eastern North Carolina and northeastern Oregon. In North Carolina, we evaluated forest and agroforestry systems using loblolly and longleaf pine species. In Oregon, we evaluated forest and agroforestry systems using ponderosa pine. We based the analyses on typical forest and cattle regimes, including yields, costs, and prices obtained from the literature, and consulted with experts in the respective subjects. The financial viability of land management investments was investigated using capital budgeting techniques. Cash flows were developed using 4 percent and 6 percent real discount rates. Analysis suggests loblolly pine timber management and cattle management are more profitable than silvopasture management in eastern North Carolina. Additionally, cattle management is more profitable than silvopasture in northeastern Oregon. Longleaf pine and ponderosa pine are not profitable when solely managed for timber and can benefit financially when combined with livestock.

Current Perspectives on Sustainable Forest Management: North America - Jacek P. Siry; Frederick W. Cubbage; Kevin M. Potter; Kathleen McGinley (Current Forestry Reports, 2018)

Greenhouse gas emissions in an agroforestry system of the southeastern USA - Alan J. Franzluebbers; Janet C. Chappell; Wei Shi; Frederick W. Cubbage (Nutrient Cycling in Agroecosystems, 2017)

Integrated beef and wood production in Uruguay: potential and limitations - Adriana Bussoni; Cabris Juan; Emilio Fernández; Mariana Boscana; Frederick Cubbage; Oscar Bentancur (Agroforestry Systems, 2015)

Comparing silvopastoral systems and prospects in eight regions of the world - Frederick Cubbage; Gustavo Balmelli; Adriana Bussoni; Elke Noellemeyer; Anibal N. Pachas; Hugo Fassola; Luis Colcombet; Belén Rossner; Gregory Frey; Francis Dube; Marcio Lopes de Silva; Hayley Stevenson; et al. (Agroforestry Systems, 2012)

Early tree growth, crop yields and estimated returns for an agroforestry trial in Goldsboro, North Carolina - Frederick Cubbage; Viola Glenn; J. Paul Mueller; Daniel Robison; Russell Myers; Jean-Marie Luginbuhl; Ron Myers (Agroforestry Systems, 2012)

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Effect of land prices, transportation costs, and site productivity on timber investment returns for pine plantations in Colombia - Juan Lopez; Rafael De La Torre; Frederick Cubbage (New Forests, 2010)

Forest Policy Reform in Brazil - Simone Bauch; Erin Sills; Luiz Carlos Estraviz Rodriguez; Kathleen McGinley; Frederick Cubbage (Journal of Forestry, 2009)
Rapid deforestation in the Brazilian Amazon, caused by economic, social, and policy factors, has focused global and national attention on protecting this valuable forest resource. In response, Brazil reformed its federal forest laws in 2006, creating new regulatory, development, and incentive policy instruments and institutions. Federal forestry responsibilities are maintained within the ministry of the environment; its regulatory agency responsibilities are divided among three different branches of the agency; many powers are delegated to states and municipalities; and a new private concession system is being developed. These reforms offer promise to improve forest protection and management in Brazil but must overcome significant institutional and social resistance for success.

Timber investment returns for selected plantations and native forests in South America and the Southern United States - Frederick Cubbage; Patricio Mac Donagh; José Sawinski Júnior; Rafael Rubilar; Pablo Donoso; Arnaldo Ferreira; Vitor Hoeflich; Virginia Morales Olmos; Gustavo Ferreira; Gustavo Balmelli; Jacek Siry; Mirta Noemi Báez; et al. (New Forests, 2007)

A Watershed-Scale Model for Predicting Nonpoint Pollution Risk in North Carolina - Kevin M. Potter; Frederick W. Cubbage; Gary B. Blank; Rex H. Schaberg (Environmental Management, 2004)

Employment and Education in Forestry: National Perspectives, North Carolina Trends - Frederick W. Cubbage; Larry G. Jervis; P. Gregory Smith (Journal of Forestry, 1999)
A comparison of data on the first jobs of one university's forestry graduates with national data on members of the foresters' professional association points to some trends in forestry employment. Compared with older alumni and with Society of American Foresters members as a whole, recent graduates from North Carolina State University are taking fewer positions with federal agencies and in land management, but more consulting jobs and specialized procurement or environmental services positions. Graduates with advanced degrees are finding more career opportunities than bachelor's-degree foresters. To prepare their graduates for future employment, forestry education programs need to reflect regional differences in employment.

Using multiple objective linear programming to evaluate multi-participant agroforestry systems - Paul A. Wojtkowski; Graham H. Brister; Frederick W. Cubbage (Agroforestry Systems, 1988)